An Exploratory Typology of MSMEs Using Dimension of Entrepreneurial and Market Orientations- The Cases of Iligan Entrepreneurs - F. Resurreccion, Pamela (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
An increasing trend in the number of registered businesses indicates a healthy business environment For Iligan City, despite an attrition rate of 15%, a slow but persistent increase in registered businesses every year appears to be due to a steady stream of nascent entrepreneurs. However, these businesses are predominantly micro in size and seem to remain so for much of its lifespan. A better understanding of the entrepreneur is important in crafting relevant and purposive policies to scaffold entrepreneurial/ aspirations and endeavour as well as programs to enhance business networks and competencies. But whet do we know about the lliganon entrepreneur? This paper contributes to the literature on local entrepreneurship by answering this question in terms of their entrepreneurial and market orientation using cluster analysis. Four distinct groups emerge to comprise the iliganon entrepreneurs.